Performance and Emission Analysis of a Diesel Engine Using Linseed Biodiesel Blends - Tunio, M. M.; Luhur, M. R.; Ali, Z. M.; Daher, U. (Engineering, Technology & Applied Science Research, 2018)
The core object of this study is to examine the suitability of linseeds for biodiesel production. The performance of an engine at different proportions of linseed blends with petro-diesel and the amount of emissions rate were investigated. Initially, linseed biodiesel was produced through transesterification process, and then it was mixed with petro-diesel fuel (D100) blends at volumetric ratios of 10% (LB10), 20% (LB20), and 30% (LB30). The properties of linseed biodiesel and its blends were investigated and compared with petro-diesel properties with reference to ASTM standards. It has been observed that the fuel properties of produced biodiesel are within ASTM permissible limits. The specific fuel consumption (SFC) of LB10 blend has been found lesser compared to LB20 and LB30. SFC of D100 is slightly less than that of all the blends. The brake thermal efficiency (BTE) of LB30 is greater than that of pure diesel D100 at maximum load and greater than that of LB10 and LB20. The heat dissipation rate in all linseed blends is found to have been less than that of D100. Carbon monoxide, carbon dioxide and NOx emissions of linseed blends are mostly lower in comparison with D100’s. Among all blends, LB10 was found more suitable alternative fuel for diesel engines and can be blended with petro diesel without engine modifications. It can be concluded that cultivation and production of linseed in Pakistan is very promising, therefore, it is recommended that proper exploitation and use of linseed for energy production may be encouraged through pertinent agencies of Pakistan.